Pembelajaran Bahasa Arab Di MIN 12 Medan - Ayu Aida Fitri; Dea Ahunaya; Dwi Rizki Amalia; Fahdhyta Nur Rahimah; Lilis Anggraini; Rizki Khairunisa Sembiring; Sapri; Syabrina Hayati Siregar (CV. ITTC INDONESIA, 2023)
Arabic is basically used to build skills in communicating socially. However, in teaching it requires a strategy that can be used to make students understand when learning Arabic. When selecting Arabic language learning strategies, you cannot just choose, but must be adjusted to the language skills to be studied. This research aims to determine the curriculum, strategies and media, as well as the difficulties of educators in teaching Arabic lessons at the MIN 12 Medan school. This paper uses qualitative research methods with data collection techniques, the data obtained comes from interviews and documentation. The results of the research show that the MIN 12 Medan school uses the 2013 curriculum, in its learning using discussion, observation and question and answer strategies, assisted by cards and puzzles to make participants more understanding and enthusiastic. The difficulties that educators encounter when teaching only lie in students who cannot write Arabic correctly